2012
DOI: 10.3329/bjms.v11i4.12598
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Tumor Lysis Syndrome with Hydration and Alkalinization in Children with Acute Lymphoblastic Leukemia

Abstract: Objective: To observe the out come of tumor lysis syndrome (TLS) following treatment with hydration and alkalinization in children with acute lymphoblastic leukemia.Methodology: This is an observational study which included 30 diagnosed ALL children who were at high risk of developing TLS in the Department of Pediatric Hematology & Oncology, BSMMU, from January 2010 to July 2010. Result: The mean (±SD) age was found 10.2±2.9 years and maximum (46.7%) numbers were found between 11 to 15 years. Male female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[11] Among the clinical symptoms the fever was the most common clinical symptoms at presentation in our study (2014) and the similar findings were reported by Khalid Hassan, et al (1993) [12] and Sultana A., et al (2010). [13] The second most common presenting clinical feature was reported as pallor (100%) by Khalid Hassan, et al (1993) and anemia by Sultana A, et al (2010) while in present study (2014) second most common presenting clinical feature was weakness (70.27%). Third most prevalent clinical feature in ALL cases was bleeding gum (73%) as reported by Khalid Hassan, et al (1993) while in our study (2014) loss of appetite was reported as third most common presenting clinical feature.…”
Section: Slnomentioning
confidence: 43%
“…[11] Among the clinical symptoms the fever was the most common clinical symptoms at presentation in our study (2014) and the similar findings were reported by Khalid Hassan, et al (1993) [12] and Sultana A., et al (2010). [13] The second most common presenting clinical feature was reported as pallor (100%) by Khalid Hassan, et al (1993) and anemia by Sultana A, et al (2010) while in present study (2014) second most common presenting clinical feature was weakness (70.27%). Third most prevalent clinical feature in ALL cases was bleeding gum (73%) as reported by Khalid Hassan, et al (1993) while in our study (2014) loss of appetite was reported as third most common presenting clinical feature.…”
Section: Slnomentioning
confidence: 43%
“…There was a reduction in the level of uric acid. It was established that the elevated level of uric acid (hyperucimea) was caused by tumor lysis syndrome (caused by the breakdown products of dying cancer cells) of leukocytes cells [ 8 ]. Stopping the beetroot-carrot juice for 1 month, then resumption of the juice for another 2 months and 11 days, leads to an increase in leukocytes and lymphocytes counts and increase in uric acid level.…”
Section: Discussionmentioning
confidence: 99%